1960
DOI: 10.1083/jcb.7.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Succinic Dehydrogenase and Cytochrome Oxidase Activities in Cell Cultures

Abstract: Succinic dehydrogenase and cytochrome oxidase have been assayed in permanent cell lines (HEP 1, HEP 2, and HLM), in short-term cultures of chick embryo heart cells, and in various tissues. Their activities in different cells are compared by relating them to deoxyribonucleic acid. They are very low in HEP 1, HEP 2, and HLM cells by comparison with the activities in any normal tissues examined. All the succinic dehydrogenase was shown to be located in the mitochondria of the permanent cell lines by staining with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1961
1961
1971
1971

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Many cells grow satisfactorily irrespective of whether oxidative or glycolytic pathways are predominant (Leslie & Jarnell, 1960). The content of cytochrome oxidase and the formation of mitochondria in cultured cells depends on oxygen partial pressure (Leslie & Jarnell, 1960;Linnae, 1965;Hakami & Pious, 1967). The described decrease in H subunit/ M subunit ratio may reflect the adaptation of cultured cells to a diminished supply of oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Many cells grow satisfactorily irrespective of whether oxidative or glycolytic pathways are predominant (Leslie & Jarnell, 1960). The content of cytochrome oxidase and the formation of mitochondria in cultured cells depends on oxygen partial pressure (Leslie & Jarnell, 1960;Linnae, 1965;Hakami & Pious, 1967). The described decrease in H subunit/ M subunit ratio may reflect the adaptation of cultured cells to a diminished supply of oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations have shown that embryonic and malignant cells in tissue culture respond to the presence of insulin. In cultures of freshly explanted embryonic-chick-heart cells insulin stimulated cell proliferation, as measured by increments in DNA phosphorus, RNA phosphorus, lipid phosphorus and protein nitrogen (Leslie & Davidson, 1951; Leslie & Paul, 1954); it also stimulated glucose uptake, but decreased total a-oxo acid production by these cells (Leslie & Paul, 1954). The hormone elicited a different response, however, in some experiments on established strains.…”
mentioning
confidence: 97%
“…and FeSO4,7H,O (0-092 mg./100 ml.). As insulin stimulates culture growth (Leslie & Paul, 1954;Leslie et al 1957), Boots Pure Drug Co. Ltd. crystalline insulin (1 unit/ml.) was included in the stock medium.…”
mentioning
confidence: 99%
See 2 more Smart Citations